Understanding of 2D human hair keratin platforms for cell culture applications - Tan, Bee Yi (Nanyang Technological University, 2020)
Human hair proteins have shown great potential in biomedical applications due to their biocompatibility, biodegradability, and more importantly their ability to promote cell adhesion and proliferation. Hair proteins consist of two main components: keratin (intermediate filaments proteins) and keratin-associated proteins (KAP, matrix proteins). The overarching aim of this project was to establish an understanding of the fundamental interaction potential within and between the two hair proteins in vitro. This understanding would then be applied to produce novel keratin-based two-dimensional (2D) substrates for biomedical applications. Specifically, hair protein-based coatings and films were targeted for development. Protein immobilization on a surface is a well-adopted method to create bioactive surfaces but the short-term stability of the coating is a limitation. Thus, total hair proteins (THP) were immobilized covalently through chemical crosslinking via free-radical assisted methods, on plasma-treated polystyrene (PS) substrates, to achieve coatings that offer long term stability. THP in the reduced form can remain as a coating for up to 21 days in media incubated at 37 °C. In addition, the reduced THP shows significantly better protein retention on the substrates after sodium dodecyl sulphate (SDS) washing, indicating stronger interactions with the PS substrates. These interactions are likely to be dominated by covalent linkages due to the presence of active thiol groups which react readily with free radicals on the activated substrate surfaces after plasma treatment. Moreover, THP is found to prefer hydrophobic adsorption onto the substrates, which might be due to the dominant hydrophobic residues in the protein sequences. Besides THP extracts, it was also intriguing to understand the interaction capacity of the keratin and KAP fractions separately. Keratin and KAP were separated successfully by modifying a previously reported protocol. A keratin film that was mechanically stable and easy-to-handle was obtained by solvent casting at room temperature. The absence of KAP was found to decrease the brittleness of the film. The films obtained were characterized for physical properties (permeability, thickness, morphology, surface wettability, etc.), mechanical properties, and thermal properties. This film was mechanically stable and exhibited 49.82 ± 6.08 MPa ultimate tensile strength (UTS) in a dry state which was nearly 50 times higher than films made with total human hair proteins with a plasticizer (1 ± 1 MPa). In the wet state, although keratin film exhibited a lower UTS 0.56 ± 0.18 MPa, it could be stretched extensively, which could never be achieved in a dry state. The tensile test results showed that the keratin film behaved as a viscoelastic material in the wet state tensile test. The keratin film also allowed 20kDa-FITC dextran to permeate in the case II diffusion mechanism. Interestingly, the keratin film showed a distinct surface and cross-sectional morphology and a protein secondary structure transformation. It is hypothesized that the keratin film could be formed by a hierarchical self-assembly process. Subsequently, keratin film was tested for basic cytocompatibility and cell physiology influences using human epidermal keratinocytes (HEKs). The keratin film was found to offer greater biocompatibility and cell response by HEKs in terms of enhanced cell proliferation, viability, K14 marker, and IL-1α cytokine, in comparison to a collagen I coating. In conclusion, the human hair protein-based coatings and keratin films could be potential platforms for biomedical applications.